2023
DOI: 10.1057/s41599-023-02117-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an evidence-based training for educators on bystander intervention for the prevention of violence against LGBTI+ youth

Oriol Rios-Gonzalez,
Juan Carlos Peña-Axt,
Guillermo Legorburo-Torres
et al.

Abstract: Research shows that teachers and educators receive scarce scientific evidence-based training and tools to implement effective strategies to stop and prevent violence against LGBTI+ youth in educational institutions. Nonetheless, no data examines pedagogical contents and training initiatives that are providing these professionals with effective strategies and skills. This paper will cover this gap by gathering data on the impact of training workshops that were carried out in five European countries as part of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 87 publications
0
1
0
Order By: Relevance
“…As a recommendation for both social work practice and research, the analyzed cases showed an improvement in the results of the practice when co-creation based on scientific evidence was applied. In other fields, including both criteria has also had a positive social impact [39,43]; therefore, it is argued that research based on co-creation without neglecting the voices of Roma participants reports positive results [10,13,41]. Regarding social work practice, previous research has made recommendations on not neglecting Roma people's voices and on developing evidence-based actions [11].…”
Section: Discussionmentioning
confidence: 99%
“…As a recommendation for both social work practice and research, the analyzed cases showed an improvement in the results of the practice when co-creation based on scientific evidence was applied. In other fields, including both criteria has also had a positive social impact [39,43]; therefore, it is argued that research based on co-creation without neglecting the voices of Roma participants reports positive results [10,13,41]. Regarding social work practice, previous research has made recommendations on not neglecting Roma people's voices and on developing evidence-based actions [11].…”
Section: Discussionmentioning
confidence: 99%
“…This has shown to foster safety, improve communication channels with diverse adults and other peers, and provide strong coordination between the school and the whole community with the goal of overcoming all types of VAC [33]. The social impact of teacher training about VAC based on scientific evidence of social impact has also been published, showing an increase among teachers of awareness of this violence and preparedness to intervene in educational settings in similar situations [41,44]. In addition, dialogic feminist gatherings, in which students read and engage in egalitarian dialogues around scientific evidence of social impact, have been demonstrated to contribute to overcoming gender-based violence among underage girls [45][46][47].…”
Section: Scientific Evidence Of the Social Impact Of Violence Against...mentioning
confidence: 99%